If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-4f + -10) = 3(2f + -4) + 2 Reorder the terms: -4(-10 + -4f) = 3(2f + -4) + 2 (-10 * -4 + -4f * -4) = 3(2f + -4) + 2 (40 + 16f) = 3(2f + -4) + 2 Reorder the terms: 40 + 16f = 3(-4 + 2f) + 2 40 + 16f = (-4 * 3 + 2f * 3) + 2 40 + 16f = (-12 + 6f) + 2 Reorder the terms: 40 + 16f = -12 + 2 + 6f Combine like terms: -12 + 2 = -10 40 + 16f = -10 + 6f Solving 40 + 16f = -10 + 6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6f' to each side of the equation. 40 + 16f + -6f = -10 + 6f + -6f Combine like terms: 16f + -6f = 10f 40 + 10f = -10 + 6f + -6f Combine like terms: 6f + -6f = 0 40 + 10f = -10 + 0 40 + 10f = -10 Add '-40' to each side of the equation. 40 + -40 + 10f = -10 + -40 Combine like terms: 40 + -40 = 0 0 + 10f = -10 + -40 10f = -10 + -40 Combine like terms: -10 + -40 = -50 10f = -50 Divide each side by '10'. f = -5 Simplifying f = -5
| 5(24.2)-32=89 | | f+k=z | | 25+25+2x=180 | | 0.1+0.9=.3-.5y | | 8-2z=10+3z | | 5y^2-9y-8=0 | | 13x+8=1x+92 | | (2b+7)(3b-c+9)= | | 4-6.25x=3.8x | | 20x-4.9x^2=0 | | 2k=-24 | | 2(5y-6)=-2 | | 5-2x+3=-8+2x | | -6y+4=76 | | 20=0.18t^3-2.16t^2+4.86t | | 9x^2+4x-44=0 | | (a-3)(6a+7)= | | 4.3=0.5 | | 5=2t | | 1-5xy^2c-3x^2+c=5xyc-4x+3x^2c | | 16-2x=-8x+10 | | (3x-1)(2x+2)= | | 12x-16=2x+14 | | 10x+3(2x+5)=5 | | 46+4x=6x+76 | | 28-3(4-x)=-2 | | 28-3(4-x)=-2 | | 28-3(4-x)=-2 | | 3x+25=40-17x | | -22-y=10 | | m^3+m^2+1=0 | | -7.5n+1.4=-6.1 |